Desain Pengembangan Kurikulum Program Studi Ilmu Falak UIN Sunan Ampel Surabaya Berbasis Integrated Twin Towers - Qulub, Siti Tatmainul (Azimuth: Journal of Islamic Astronomy, 2020)
Abstrak: Artikel ini dimaksudkan untuk mengetahui integrasi antara Ilmu Falak dan astronomi dalam kurikulum Ilmu Falak, dan mendesain pengembangan kurikulum Ilmu Falak di UIN Sunan Ampel Surabaya yang berbasis integrated twin towers. Integrasi ilmu falak dan astronomi pada prodi studi ilmu falak sudah tampak pada level materi. Sebaran mata kuliah yang diberikan dalam pembelajaran di prodi ilmu falak memasukkan rumpun ulmu ilmu falak dan ilmu astronomi. Rumpun ilmu falak seperti Pengantar Ilmu Falak, Fiqh Mawaqit, Tafsir Ayat Hukum Falak, Hadis Hukum Falak, Sistem Penanggalan, Hisab Arah Kiblat & Waktu Shalat, Hisab Awal Bulan Qamariyah, Hisab Gerhana Bulan, Hisab Gerhana Matahari, Perangkat Rukyat Non-Optik, Perangkat Rukyat Optik, Kajian Teks Kitab Ilmu Falak, Praktikum Falak, dan Praktik Hisab dan Rukyah. Adapun rumpun ilmu astronomi meliputi; Dasar-Dasar Astronomi, Astronomi, Dasar-Dasar Astronomi Bola, Astronomi Bola, Dasar-Dasar Astrofisika, Astrofisika, Matematika, Studi Hisab dan Rukyat di Pelbagai Negara, Astronomi dan Kebudayaan. Adapun pada level filosofis dan strategi pembelajaran, integrasi keilmuan tidak terlalu tampak. Kedua, Desain kurikulum prodi ilmu falak dalam paradigma integrated twin towers diupayakan pada level materi dan metode pembelajaran. Level materi dan pembelajaran berjalan secara beriring. Kata Kunci: Ilmu Falak, Astronomi, Kurikulum Berbasis Integrated Twin Towers Abstract: This article was intended to determine the integration between Falak Science and astronomy in the Falak Science curriculum, and design the development of the Falak Science curriculum at UIN Sunan Ampel Surabaya based on integrated twin towers. The integration of falak and astronomy in astronomy study programs appeared at the material level. The distribution of courses given in learning at the astronomy study program includes the ul clump of astronomy and astronomy. Falak clusters such as Introduction to Falak Science, Mawaqit Fiqh, Falaf Law Interpretation, Falak Law Hadith, Calendar System, Reckoning of Qibla Direction & Prayer Times, Preliminary Reckoning of Qamariyah, Reckoning of Moon Eclipse, Reckoning of Sun Eclipse, Non-Optic Ruling Hadith, Calendar System, Reckoning of Qibla Direction & Prayer Times, Preliminary Reckoning of Qamariyah, Reckoning of Moon Eclipse, Reckoning of Solar Eclipse, Non-Optic Ruling Hadith, Devices Rukyat Optik, Text Study of the Book of Falak Science, Falak Practicum, and Hisab and Rukyah Practices. The astronomy family includes; Basics of Astronomy, Astronomy, Basics of Ball Astronomy, Ball Astronomy, Basics of Astrophysics, Astrophysics, Mathematics, Hisab and Rukyat Studies in Various Countries, Astronomy and Culture. As for the philosophical and learning strategy levels, scientific integration is not very visible. Second, the curriculum design of the celestial study program in the integrated twin towers paradigm is pursued at the level of material and learning methods. Material and learning levels go hand in hand. Keywords: Falak Science, Astronomy, Integrated Twin Towers Curriculum